An overview on problems in handling day to day foreign trade transaction in Al‐ ArafahIslami Bank Ltd and solutions there of - Mazumder, Hasan Mahamud (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2015.